Weight gain in type 1 diabetes during the SARS-CoV-2 pandemic. Does lockdown affect the metabolic control of pediatric patients? - Zubkiewicz-Kucharska, Agnieszka; Wikiera, Beata; Noczyńska, Anna (Frontiers in Endocrinology, 2022)
Background and Aims: Due to the SARS-Cov-2 pandemic, governments of many countries, decided to implement the lockdown, which included schools' closure. This major lifestyle change also applies to people with diabetes. The aim of this paper was to analyze how COVID-19 pandemic and related restrictions influenced metabolic compensation of diabetes in pediatric population. Methods: Patients with type 1 diabetes, treated by one therapeutic team, who in 2020 and 2021 paid at least two in-person visits in the outpatient clinic, were included into the study. Time In Range (TIR), and HbA1c, as well as Total Daily Dose of insulin (TDD) and BMI from the visit before the announcement of the pandemic restrictions (March 2020) and during the lockdown (second visit after 6 months) and within period of loosened restrictions (two visits in 2021) were analyzed. Results: 185 patients with type 1 diabetes were included into the study (96 boys), aged 2-18 years (11.5±3.5), 135 of them (72.9%) use CSII, 142 (76.8%) use CGM or FGM. During the first months of studied period, despite comparable TIR (57.5±21.4% vs. 59.9±20.5%; p>0.05), improvement of HbA1c was noticed (7.9±1.6% vs. 7.5±1.4%; p=0.0336), while in the following months both HbA1c and TIR were comparable. Also, TDD increased significantly, from the first visit to the last visit (37.3±18.9 units/day vs. 46.8±22.7 units/day; p=0.0003), however TDD / kg remained constant (0.8±0.2 units/kg/day vs. 0.8±0.3 units/kg/day; p>0.05), possibly due to increased BMI (19.1±3.7 kg/m2 vs. 20.9±4.1 kg/m2; p=0.0001). % of basal insulin in TDD remained stable (39.7±11.3% vs. 39.3±13.6%; p>0.05). Furthermore, a significant change of BMI percentile was noticed from the visit before lockdown to the second visit (58.9±26.2%ile vs. 64.6±26.0 %ile; p=0.0001). However, BMI percentile returned to baseline (58.1±28.4 %ile) at the visit at the end of the observation period. Conclusions: The parameters of metabolic control in pediatric patients with type 1 diabetes during the pandemic period remained stable; however weight gain and an increase in daily insulin dose have been observed, possibly due to reduced physical activity during lockdown.